Problem-solving activity including trust and honesty: spotlighting ‘ASD’ students - Janiec, Jerzy (Kultura-Społeczeństwo-Edukacja, 2018)
How many times dear reader have you found yourself in a quite challenging situation (having an ambitious student, but with depression, social, emotional and interaction deficits, low self-esteem, OCD and everything connected with ASD) when the most crucial was timing (15 weeks and the same amount of subjects to pass by the given learner) and you have been looking for possible solutions without any further favorable outcomes wondering what should be another step of mine as educator in the upcoming end of the school year? This paper is some sort of answer on the given questions providing a far-reaching suggestion, after in-depth reflection and evaluation, for individual creative work in order to understand ASD students. Sometimes we need to give ‘three steps back to move one step forward’. Three steps back is a diligent investigation that consists of four stages, namely stage of novitiate (refocus), stage of puzzles, and stage of fixing the puzzles and stage of creativity. What’s more, we need to reflect on our thoughtfulness by analyzing acronym C.A.M.P.A.I.G.N.E.R. with specific personality traits. Possessing background knowledge about the problem and ourselves we can move forward by implementing creatively possible solutions to our circumstances remembering about being in every situation ourselves.